PERBANDINGAN ANTARA UNDANG-UNDANG NOMOR 13 TAHUN 2003 KETENAGAKERJAAN DENGAN UNDANG-UNDANG NOMOR 11 TAHUN 2020 CIPTA KERJA DALAM PEMUTUSAN HUBUNGAN KERJA BAGI PEKERJA PERJANJIAN KERJA WAKTU TERTENTU PADA MASA KONTRAK - Poernamadjaja, Doddy; Hufron, Hufron (Mimbar Keadilan, 2022)
the aim of this research was conducted analyze legal protection for workers' contracts, who are dismissed before the end of their working period. This research was conducted using juridical-normative legal research, The research produces the first answer PKWT workers who are dismissed based on the employees have not provided maximum legal protection for PKWT workers, Article 62 of the employment only provides compensation for workers/ laborers. workers until the end of the work agreement. The attestation of the Job Creation Law and PP 35 of 2021 raises legal problems in the form of conflicting norms (antinomy norms) and does not reflect legal protection in the theory of equitable legal objectives. requires employers to provide compensation in the amount of which is based on the period of PKWT that has been implemented. by the Employer. hen based on the results of the research, the norm of Article 16 PP 35 of 2021 is contrary to a higher norm, namely Article 62 of the employment of Law.